Managing Conflicts with Wildlife: Living with Snakes - Holly K. Ober; Steve A. Johnson; William M. Giuliano (EDIS)
Snakes provide many benefits to people and to the environment. They control rat and mice populations in the environment, for example, and in the laboratory, pygmy rattlesnake venom research helped develop medicine to thin the blood of heart attack patients. Most snakes are secretive and rarely bother people, but in some situations some snakes can become dangerous. In this 4-page fact sheet, we present some facts about snakes, describe dangers they may cause, and provide suggestions on how to cope with these dangers. Written by Holly K. Ober, Steve Johnson, and William M. Giuliano, and published by the UF Department of Wildlife Ecology and Conservation, November 2014. Updated November 2023 to reflect a change in recommendations. (Glue traps must not be used to remove snakes.) (Photo: Steve Johnson) WEC350/UW395: Managing Conflicts with Wildlife: Living with Snakes (ufl.edu)